Two giants of geology: Kevin Charles Antony Burke and John Frederick Dewey - Şengör, A.M. Celâl; Polat, Ali (Canadian Science Publishing, 2016)
This special issue of the Canadian Journal of the Earth Sciences celebrates the career of two of the greatest geologists of our time, who, during the last three decades of the 20th and the first decade of the 21st century, have put their stamp on the tectonic interpretation of the Earth’s behaviour (Burke also extended his efforts into extra-terrestrial space). How fortunate it is for geology that they are both still active and, by all appearances, are likely to remain so for some time to come. It is an immense honour for us as their students and fellow geologists to introduce this special issue with a few lines about them whom we have had the great privilege of knowing closely both as colleagues and as friends. In the late 1960s, few geologists grasped the significance of plate tectonics because a broad view of the geological behaviour of our planet was the first necessity to be able to do so. In the 1960s, there were a number of such geologists with an encyclopaedic knowledge of global geology, yet not many of them became a Kevin Burke or John Dewey, because they lacked the other, in our view the more critical, component of a broad world-view of geology: A critical rational approach, i.e., the courage to ask the question: what ought it to be like? Such a question had long been anathema in the 20th century geology because of the prevalent Baconianism. As Tuzo Wilson wrote in his own autobiography “more geological mapping was both the method and the aim of geology” in those days. Most geologists in the 20th century were instructed to learn “the basic principles” first and then be ready to question the data. However, those very principles that they were advised to learn (implicitly, without questioning) were the …